1997
DOI: 10.1007/bf03341095
|View full text |Cite
|
Sign up to set email alerts
|

Serious Emotional Disturbance and Social Maladjustment: A Critical Examination of Four Schools of Thought

Abstract: Issues related to inclusion of youths with social maladjustment (SM) in the category of serious emotional disturbance (SED) are examined. Differing views advocated in professional literature are conceptualized into four schools of thought: (I) The exclusion perspective conceptualizes SM as behavior disorders and advocates for exclusion from special education services; (2) The delinquence perspective defines SM as delinquent behaviors and excludes virtually all students exhibiting these behaviors from services;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For example, the debate as to whether services should be provided to youths considered to have social maladjustment (or "troubling") issues versus youth with SED (or "troubled" behaviors) has been a constant policy theme over the years, especially in the educational sector (for a more detailed review, refer to Rosenblatt & Furlong, 1997). The current study has empirically validated that as many as four different clusters of youth exist across all agency subpopulations.…”
Section: Differences In Profiles Of Youth Across Clustersmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, the debate as to whether services should be provided to youths considered to have social maladjustment (or "troubling") issues versus youth with SED (or "troubled" behaviors) has been a constant policy theme over the years, especially in the educational sector (for a more detailed review, refer to Rosenblatt & Furlong, 1997). The current study has empirically validated that as many as four different clusters of youth exist across all agency subpopulations.…”
Section: Differences In Profiles Of Youth Across Clustersmentioning
confidence: 69%
“…For example, services for children considered to have social maladjustment (SM) characteristics have been denied in some educational settings (Slenkovich, 1992) and/or relegated exclusively to juvenile justice systems. This trend appears to be due to rigid interpretation of federal eligibility criteria for special education that attempts to discriminate children with "troubled" (those youth with SED in need of mental health and special education services) from children with "troubling" (those youth requiring correctional interventions) behaviors (Rosenblatt & Furlong, 1997). Initially coined by Hobbs (1982), the term troubled generally refers to youth with internalizing and emotional difficulties, while the term troubling refers to youth with externalizing and acting-out behaviors.…”
mentioning
confidence: 94%
“…The Individuals with Disabilities Education Act (IDEA) definition of emotional disturbance provides little guidance in the identification and treatment of this population of children. The definition is vague and contains controversial language (Rosenblatt & Furlong, 1997) in addition to including children with a variety of internalizing, externalizing, and comorbid behavior problems (Stinnett, Bull, Koonce, & Aldridge, 1999).…”
Section: Assessment Of Students Displaying Behavioral Problemsmentioning
confidence: 99%
“…Besides the ongoing controversial identification guidelines and the disparate manner in which they can be interpreted (Rosenblatt & Furlong, 1997), orher reasons have been postulated to explain the variation in state identification rates of E/BD. Coutinho and Denny (1 996) suggested that numerous factors may affect the fidelity, interpretability, and comparability of placement rates.…”
mentioning
confidence: 99%